'Building back better' is neoliberal post‐disaster reconstruction. Issue 3 (5th May 2022) - Cheek, Wesley; Chmutina, Ksenia
Abstract : 'Building back better' (BBB) has become one of the most common expressions in disaster risk reduction. Disasters offer an opportunity to encourage improvements not only in the structural safety of buildings and infrastructure, but also in addressing structural inequalities and injustice. Consequently, they are an opportunity to make things 'better'. However, in the context of neoliberalism, the definition of 'better' does not always mean 'good for all'. We argue here that BBB allows for widely varied definitions of what is and what is not a risk, who is and is not responsible, and what forms of action are to be taken in response to these dangers. This serves as a designation for capacity to make 'better', but not actively change, social and political systems that initially create risk. Disasters and its terminology, therefore, are not ideologically neutral and should thus be deliberately unpacked and critically evaluated rather than accepted unquestioned. نبذة مختصرة: 本文对2018年洪水后库塔纳德地区 (印度南部一处海平面以下农业系统)农户的生产资料易损度方面进行了研究为此，我们利用从各户采集到的各种应对策略的严重程度和频率的数据，构建了一种应对策略强度的衡量标准——洪水应对策略指数（FCSI）。此外，我们估算了一个Tobit回归模型，以确定影响应对策略选择强度的因素。FCSI结果表明，由于州政府快速有效的政策反应，只有2‰的农户的易受损度达到了"严重"程度。此外，Tobit回归分析表明，女性户主家庭和劳动力家庭相对更易受损。虽然收入对生产资料易损度有负影响，但农业土地增加了洪水期间的耕作损失，因此对易损度有正影响 关键词： 洪水，农业，脆弱性，洪水应对策略指数，Tobit回归模型，Kuttanad 摘要: أصبح "إعادة البناء بشكل أفضل" أحد أكثر الشعارات شيوعًا في "الحد من مخاطر الكوارث". توفر الكوارث فرصة لتشجيع التحسينات ليس فقط في السلامة الهيكلية للمباني والبنية التحتية ولكن أيضًا في معالجة أوجه عدم المساواة الهيكلية والظلم ‐ أي الأسباب الجذرية للكوارث. وبالتالي فإن الكوارث هي فرصة لتحسين الأمور. ومع ذلك، كما ستوضح هذه الورقة، في سياق النيوليبرالية، فإن تعريف "أفضل" في شعار الحد من مخاطر الكوارث لا يعني دائمًا "جيد للجميع". من خلال استكشاف التطورات الموازية في تطور الحد من مخاطر الكوارث والليبرالية الجديدة، نجادل بأن «إعادة البناء بشكل أفضل» ودعواتها لإعادة بناء الاقتصاد والبنية التحتية وتنشيط الموارد البشرية تسمح بتعريفات متنوعة على نطاق واسع لما هو خطر وما هو ليس كذاك، ومن هو مسؤول وغير مسؤول، وما هي الخطط التي يجب اتباعها للاستجابة لهذه المخاطر. هذا بمثابة تعيين للقدرة على جعل النظم الاجتماعية والسياسية "أفضل" ‐ ولكن ليس التغيير الفعال ‐ الذي يخلق المخاطر في المقام الأول. لذلك نظهر أن الكوارث ‐ والمصطلحات المستخدمة في خطاب الكارثة ‐ ليس محايدًا أيديولوجيًا وبالتالي يجب تفكيكه وتقييمه بشكل نقدي عمدًا بدلاً من قبوله دون نقاش. الكلمات المفتاحية : إعادة البناء بشكل أفضل، الحد من مخاطر الكوارث، الليبرالية الجديدة.